Titanium implant, its preparation method and application

CN117482284BActive Publication Date: 2026-10-20HOSPITAL OF STOMATOLOGY SUN YAT SEN UNIV +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311349356.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-18
Publication Date
2026-10-20
Estimated Expiration
2043-10-18

AI Technical Summary

Technical Problem

然而,如图1所示,钙磷涂层沉积难以控制,往往会破坏纳米管形貌,使得原本高度有序的纳米管形貌不可避免的模糊、甚至消失,降低纳米管形貌本身对参与骨结合的多种细胞、蛋白的调控作用,导致复合改性的协同效应降低

Benefits of technology

[0033]本发明提供的钛种植体的表面自内向外依次包括纳米管层、纳米栅层和钙磷涂层,其中纳米管层中的纳米管的平均直径为30-40nm,纳米栅层中纳米栅的平均直径为60-80nm,即纳米管层中纳米管的平均直径小于纳米栅层中纳米栅的平均直径,从而能够形成完整的双层纳米结构,且能避免纳米栅对纳米管的遮蔽作用,并且钙磷涂层附着在纳米栅层的栅格边缘,进一步确保了纳米管不被遮蔽,从而能够保持完整的纳米管形貌,确保形貌作用得到充分的发挥,且选择的纳米栅平均直径范围也具有优异的骨传导性,CaHPO4涂层具有优异的溶解性;即本发明的钛种植体通过对结构和成分优化,能够取得优异的骨结合能力。并且本发明提供的钛种植体的制备方法工艺简单、操作方便,易于实际生产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117482284B_ABST
    Figure CN117482284B_ABST
Patent Text Reader

Abstract

The application discloses a titanium implant, a preparation method and application thereof, and belongs to the technical field of medical materials; the titanium implant provided by the application comprises, from inside to outside, a nanotube layer, a nanogrid layer and a calcium phosphate coating layer; the average diameter of the nanotubes in the nanotube layer is 30-40 nm; the average diameter of the nanogrids in the nanogrid layer is 60-80 nm; and the calcium phosphate coating layer is a CaHPO4 coating layer. The titanium implant provided by the application has excellent bone combination capacity, and the preparation method of the titanium implant is simple in process, convenient to operate and easy to produce in practice.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of medical materials technology, and particularly relates to a titanium implant, its preparation method and application. Background Technology

[0002] Dental implant restoration has been widely used in the treatment of patients with missing teeth and edentulous teeth due to its excellent masticatory and aesthetic restoration effects. However, in conventional implant restoration, titanium implants require approximately 3 months to form osseointegration, resulting in a long overall treatment cycle. The success and rate of implant osseointegration are closely related to its surface properties and are one of the main factors affecting the implantation process and efficacy. To meet the clinical needs of accelerating healing and shortening the treatment cycle, surface modification has become a research focus in the field of dental implantology.

[0003] Implant surface modification is simple, effective, safe, controllable, and durable, mainly falling into two categories: the first is constructing biomimetic coatings loaded with bioactive elements or molecules; the second is improving surface morphology. Currently, many studies combine these two modification methods to create composite surface modifications, hoping to leverage their synergistic effects. In constructing bioactive coatings, calcium phosphate coatings have been extensively studied due to their chemical composition being consistent with bone tissue. Calcium phosphate coatings can improve the mechanical properties of materials, enhance surface hydrophilicity, and provide matrix mineralization raw materials, ultimately accelerating osseointegration. Regarding improving surface morphology, the morphology of titanium dioxide nanotubes can increase surface area, enhance surface adsorption capacity, generate unique biointerface interactions, and improve biocompatibility; simultaneously, the special hollow tubular structure of titanium dioxide nanotubes is conducive to further functionalization, making them highly favored in composite modification. Therefore, preparing calcium phosphate coatings based on nanotube morphology to form calcium phosphate / nanotube composite layers has become a hot topic in titanium implant surface modification. Studies by Parcharoen et al. have shown that nanotubes, as an intermediate layer, can improve the bonding strength between the calcium phosphate coating and the titanium substrate, and withstand the stress generated by bone growth. Bose et al. observed accelerated new bone formation around 3D-printed porous titanium implants with a calcium-phosphorus / nanotube composite layer. However, as Figure 1 As shown, calcium phosphate coating deposition is difficult to control and often damages the nanotube morphology, inevitably blurring or even eliminating the originally highly ordered nanotube morphology. This reduces the regulatory effect of the nanotube morphology on various cells and proteins involved in bone integration, leading to a decrease in the synergistic effect of composite modification. Therefore, ensuring the integrity of the nanotube morphology during calcium phosphate coating deposition is a key technical challenge in constructing calcium phosphate / nanotube composite structures. Summary of the Invention

[0004] The purpose of this invention is to overcome the shortcomings of the prior art and provide a titanium implant with a simple process, capable of depositing a calcium phosphate coating while protecting the intact morphology of nanotubes, and having excellent ability to accelerate bone integration, as well as its preparation method and application.

[0005] To achieve the above objectives, in a first aspect of the present invention, the present invention provides a titanium implant, wherein the surface of the titanium implant comprises, from the inside out, a nanotube layer, a nanogate layer and a calcium phosphate coating.

[0006] The average diameter of the nanotubes in the nanotube layer is 30-40 nm.

[0007] The average diameter of the nanogates in the nanogate layer is 60-80 nm.

[0008] The calcium phosphate coating is a CaHPO4 coating.

[0009] The titanium implant provided by this invention comprises, from the inside out, a nanotube layer, a nanogrid layer, and a calcium phosphate coating. The nanotube layer retains the complete morphology of the nanotubes, which plays a regulatory role on various cells and proteins involved in bone integration and enhances the synergistic effect of composite modification. As a result, the prepared titanium implant has excellent bone integration promotion ability. Specifically, the titanium implant provided by this invention has nanotubes in the nanotube layer with an average diameter of 30-40 nm and nanogrids in the nanogrid layer with an average diameter of 60-80 nm. This means the average diameter of the nanogrids in the nanogrid layer is larger than the average diameter of the nanotubes in the nanotube layer. This reduces the shielding effect of the nanogrids on the nanotubes, preventing the formation of a bilayer structure due to their similar diameters. Furthermore, the electric field of the nanogrids ensures that the calcium phosphate coating is deposited only at the edges of the grid, further minimizing its influence on the nanotube morphology and allowing the nanotubes to fully utilize their morphological function, providing an ideal bone immune environment for bone regeneration. Simultaneously, the nanogrids within the corresponding average diameter range also exhibit good biological properties, especially excellent osteoconductivity. In addition, the calcium phosphate coating of this invention is a CaHPO4 coating, which is more soluble than conventionally used hydroxyapatite coatings and thus more readily exerts its biological effects. Therefore, with the combination and modification of the above structures, the resulting titanium implant exhibits excellent overall performance.

[0010] In a preferred embodiment of the titanium implant of the present invention, the average diameter of the nanogrid in the nanogrid layer is more than twice the average diameter of the nanotube in the nanotube layer.

[0011] The inventors discovered that when the average diameter of the nanogate in the nanogate layer is further controlled to be more than twice the average diameter of the nanotube in the nanotube layer, the morphology of the nanotube can be better preserved, and its function can be fully utilized.

[0012] In a preferred embodiment of the titanium implant of the present invention, the thickness of the nanotube layer is 300-400 nm;

[0013] And / or, the thickness of the nanogate layer is 5-15 nm;

[0014] And / or, the thickness of the calcium phosphate coating is 10-20 nm.

[0015] The inventors discovered that when the thicknesses of the nanotube layer, nanogate layer, and calcium phosphate coating are within the aforementioned range, the overall effect is even better.

[0016] In a second aspect of the present invention, the present invention provides a method for preparing the titanium implant, the method comprising the following steps: performing a first anodizing on the surface of a titanium implant substrate followed by ultrasonic vibration, and then sequentially performing a second anodizing and electrochemical deposition to obtain a titanium implant.

[0017] In the preparation method provided by this invention, anodizing can prepare nanotube morphologies. During anodizing, an oxide layer is first generated through field-induced oxidation. Subsequently, field-induced dissolution and chemical dissolution compete with each other, and the surface oxide layer generates pore cores, which gradually expand into micropores and dissolve downwards to grow, ultimately forming ordered nanotubes. This invention uses two anodizing processes. After the first anodizing process, ultrasonic vibration is performed to remove the nanotubes from the first anodizing process, forming a corresponding uniform and ordered nanogrid structure. Then, a second anodizing process is performed, and based on the formed nanogrid structure, corresponding nanotubes are formed downwards. The nanotube structure is obtained by controlling parameters such as voltage, time, and electrolyte composition during two anodizing processes, thereby obtaining a composite structure of nanotubes and nanogrids with diameters within the range given in this invention. Furthermore, an electrochemical deposition process is used to introduce a calcium phosphate coating. During the electrochemical deposition and composite modification of the nanotube or nanogrid surface, nanoparticles preferentially deposit at the edges of the nanotube or nanogrid walls due to a stronger electric field. Since the nanogrid is on the outer layer of the nanotube and its average diameter is greater than the average diameter of the nanotube, the calcium phosphate coating preferentially deposits at the grid edges of the nanogrid, thus protecting the morphology of the nanotube from being affected.

[0018] In a preferred embodiment of the preparation method described in this invention, in the first anodic oxidation, the anode is a titanium implantation substrate, the cathode is pure titanium, the electrolyte is an ethylene glycol solution containing 0.2-0.4 wt% NH4F and 1.5-2.5 vol% water, the oxidation voltage is 50-70 V, and the oxidation time is 15-25 min.

[0019] Preferably, in the first anodic oxidation, the anode is a titanium implantation substrate, the cathode is pure titanium, the electrolyte is an ethylene glycol solution containing 0.3 wt% NH4F and 2.0 vol% water, the oxidation voltage is 60 V, and the oxidation time is 20 min.

[0020] The selection of parameters for the first anodizing process affects the diameter of the nanogates in the subsequently formed nanogate layer. The inventors have found that when the parameters for the first anodizing process are selected within the above-mentioned range, the average diameter of the nanogates in the obtained nanogate layer can be guaranteed to be between 60-80 nm.

[0021] In a preferred embodiment of the preparation method described in this invention, the ultrasonic power during ultrasonic oscillation is 180-200W and the ultrasonic time is 25-35min.

[0022] Preferably, in the ultrasonic oscillation, the ultrasonic power is 200W and the ultrasonic time is 30min.

[0023] The ultrasonic oscillation process can transform the large-pore nanotubes formed by the first anodizing into corresponding nanogrid structures, that is, it can remove the corresponding large-pore nanotubes to obtain a uniform and ordered thin-layer nanogrid. When the ultrasonic oscillation parameters are further selected, the nanotubes can be removed better to form a more uniform and ordered nanogrid structure.

[0024] In a preferred embodiment of the preparation method described in this invention, in the second anodic oxidation, the anode is a titanium implantation substrate after ultrasonic vibration, the cathode is pure titanium, the electrolyte is an ethylene glycol solution containing 0.2-0.4 wt% NH4F and 1.5-2.5 vol% water, the oxidation voltage is 20-40 V, and the oxidation time is 50-70 min.

[0025] Preferably, in the second anodic oxidation, the anode is a titanium implantation substrate subjected to ultrasonic vibration, the cathode is pure titanium, the electrolyte is an ethylene glycol solution containing 0.3 wt% NH4F and 2.0 vol% water, the oxidation voltage is 30 V, and the oxidation time is 60 min.

[0026] The second anodizing can form small-pore nanotubes. When the parameters of the second anodizing are selected within the above range, it can be ensured that the average diameter of the nanotubes in the obtained nanotube layer is 30-40 nm.

[0027] In a preferred embodiment of the preparation method described in this invention, the electrochemical deposition uses platinum as the anode, titanium as the cathode after second anodic oxidation, and an aqueous solution containing 0.04-0.06 mol / L NaNO3, 0.18-0.22 mmol / L Ca(NO3)2 and 0.10-0.14 mmol / L (NH4)2HPO4, with an initial potential of (-2)-(-4) V.

[0028] In a preferred embodiment of the preparation method described in this invention, the electrochemical deposition temperature is 70-90℃ and the electrochemical deposition time is 700-900s.

[0029] Preferably, in the electrochemical deposition, the anode is platinum, the cathode is a titanium implantation substrate after second anodic oxidation, the electrolyte is an aqueous solution containing 0.05 mol / L NaNO3, 0.20 mmol / L Ca(NO3)2, and 0.12 mmol / L (NH4)2HPO4, the initial potential is (-3) V, the electrochemical deposition temperature is 80 °C, and the electrochemical deposition time is 800 s.

[0030] The selection of electrochemical deposition parameters affects the distribution and thickness of the calcium phosphate coating. The inventors have found that when the selected electrochemical deposition parameters are within the above range, the formation of the calcium phosphate coating can avoid obscuring the nanotubes, thereby maintaining the complete morphology of the nanotubes. In addition, the present invention selects CaHPO4 as the specific component of the electrolyte after electrochemical deposition. The obtained CaHPO4 coating has better solubility and can better perform its corresponding function.

[0031] In a third aspect, the present invention provides the use of the titanium implant in the preparation of medical implant materials.

[0032] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0033] The titanium implant provided by this invention comprises, from the inside out, a nanotube layer, a nanogrid layer, and a calcium phosphate coating. The average diameter of the nanotubes in the nanotube layer is 30-40 nm, and the average diameter of the nanogrids in the nanogrid layer is 60-80 nm. This means the average diameter of the nanotubes in the nanotube layer is smaller than the average diameter of the nanogrids in the nanogrid layer, thus forming a complete bilayer nanostructure and avoiding the shading effect of the nanogrids on the nanotubes. Furthermore, the calcium phosphate coating adheres to the grid edges of the nanogrid layer, further ensuring that the nanotubes are not obscured, thereby maintaining the complete nanotube morphology and ensuring that the morphology effect is fully utilized. The selected average diameter range of the nanogrids also exhibits excellent osteoconductivity, and the CaHPO4 coating has excellent solubility. In other words, the titanium implant of this invention, through structural and compositional optimization, achieves excellent bone integration. Moreover, the preparation method of the titanium implant provided by this invention is simple, convenient to operate, and easy to implement in actual production. Attached Figure Description

[0034] Figure 1 The image shows the microstructure of a titanium implant formed using the prior art, as provided in the background section.

[0035] Figure 2 A schematic diagram of the structure of the titanium implant provided by this invention:

[0036] 1-Calcium phosphate coating, 2-Nano barrier layer, 3-Nanotube layer, 4-Titanium implant surface layer;

[0037] Figure 3 This is a schematic diagram of the preparation process of the titanium implant provided in an embodiment of the present invention;

[0038] Figure 4 This is a surface morphology diagram of the titanium implant substrate after the first anodizing treatment in Example 1;

[0039] Figure 5 This is a surface morphology image of the titanium implant substrate after ultrasonic vibration in Example 1;

[0040] Figure 6 This is a surface morphology diagram of the titanium implant substrate after the second anodizing treatment in Example 1;

[0041] Figure 7 The image shows the surface morphology of the titanium implant prepared in Example 1.

[0042] Figure 8 This is an EDS (Electrode Spectroscopy) result of the calcium phosphate coating on the surface of the titanium implant prepared in Example 1.

[0043] Figure 9 This is an XPS image showing the results of the calcium phosphate coating on the surface of the titanium implant prepared in Example 1.

[0044] Figure 10 The image shows the surface morphology of the titanium implant prepared in Comparative Example 1.

[0045] Figure 11 The image shows the surface morphology of the titanium implant prepared in Comparative Example 2.

[0046] Figure 12 The surface morphology of the titanium implant prepared in Comparative Example 3 is shown in the figure.

[0047] Figure 13 The image shows the surface morphology of the titanium implant prepared in Comparative Example 4.

[0048] Figure 14 Image of the implant used in the effect example:

[0049] A is the implant design drawing, and B is a picture of the actual implant.

[0050] Figure 15 Animal experiments were conducted on the negative control group in the effect example and the titanium implants prepared in Example 1. The results of the Micro-CT three-dimensional reconstruction model were obtained at 4 weeks and 8 weeks.

[0051] Figure 16 The images show the results of animal experiments conducted at 4 and 8 weeks on hard tissue sections stained with methylene blue-acid fuchsin for the negative control group in the effect example and the titanium implants prepared in Example 1. Detailed Implementation

[0052] To better illustrate the purpose, technical solution, and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0053] Unless otherwise specified, the reagents, methods and equipment used in this invention are all conventional reagents, methods and equipment in the field.

[0054] Example 1

[0055] This invention provides a titanium implant, the structural schematic of which is shown in the figure below. Figure 2 The titanium implant surface comprises, from the inside out, a nanotube layer, a nanogrid layer, and a calcium phosphate coating. The nanotube layer has an average diameter of 35 nm and a thickness of 350 nm. The nanogrid layer has an average diameter of 70 nm and a thickness of 10 nm. The calcium phosphate coating is a CaHPO4 coating with a thickness of 15 nm.

[0056] The schematic diagram of the preparation process of the titanium implant is shown below. Figure 3 As shown, specifically, the preparation method of the titanium implant includes the following steps:

[0057] (1) First anodic oxidation treatment: The titanium planting substrate is used as the anode, pure titanium is used as the cathode, and the electrolyte is an ethylene glycol solution containing 0.3wt% NH4F and 2.0vol% water. The anodic oxidation treatment is carried out at a constant voltage of 60V for 20min.

[0058] (2) Ultrasonic vibration treatment: The titanium implant substrate after the first anodization was placed in deionized water and ultrasonicated at an ultrasonic frequency of 200W for 30 minutes.

[0059] (3) Second anodic oxidation treatment: The ultrasonically vibrated titanium implantation substrate is used as the anode, pure titanium is used as the cathode, and the electrolyte is an ethylene glycol solution containing 0.3wt% NH4F and 2.0vol% water. The anodic oxidation treatment is carried out at a constant voltage of 30V for 60min.

[0060] (4) Electrochemical deposition treatment: The titanium implant substrate after the second anodic oxidation treatment is used as the cathode, the platinum sheet is used as the anode, the electrolyte is an aqueous solution containing 0.05 mol / L NaNO3, 0.20 mmol / L Ca(NO3)2, 0.12 mmol / L (NH4)2HPO4, and an initial voltage of -3V. Electrochemical deposition is carried out in a water bath at 80℃ for 800s to obtain the titanium implant.

[0061] In the preparation process of Example 1, the surface morphology of the product obtained in each step was observed. The surface morphology image of the titanium implant substrate after the first anodizing treatment is shown below. Figure 4 As shown, from Figure 4As can be seen, a nanotube structure was formed; the surface morphology of the titanium implant substrate after ultrasonic vibration is shown in the figure below. Figure 5 As shown, from Figure 5 As can be seen, a uniform and ordered nanogrid structure is formed through ultrasonic vibration treatment; the surface morphology of the titanium implant substrate after the second anodizing treatment is shown in the figure. Figure 6 As shown, from Figure 6 As can be seen, a nanotube structure layer with small pores is formed beneath the nanogate; the surface morphology of the final prepared titanium implant is shown in the figure. Figure 7 As shown, from Figure 7 It can be seen that the calcium phosphate coating is mainly deposited at the lattice edge of the nanogrid, and a complete nanotube morphology can be observed; the EDS and XPS detection results of the calcium phosphate coating on the surface of the prepared titanium implant are as follows: Figure 8 , Figure 9 As shown, from Figure 8 , Figure 9 As can be seen, the obtained calcium phosphate coating is a CaHPO4 coating.

[0062] Meanwhile, the elemental content information of the surface of the titanium implant prepared in Example 1 of this invention was obtained through testing and is shown in Table 1.

[0063] Table 1

[0064] Titanium implants 58.47% 41.15% 0.21% 0.16%

[0065] Example 2

[0066] This invention provides a titanium implant, the surface of which, from the inside out, comprises a nanotube layer, a nanogrid layer, and a calcium phosphate coating. The nanotube layer has an average diameter of 30 nm and a thickness of 400 nm. The nanogrid layer has an average diameter of 60 nm and a thickness of 10 nm. The calcium phosphate coating is a CaHPO4 coating with a thickness of 15 nm.

[0067] The preparation method of the titanium implant includes the following steps:

[0068] (1) First anodic oxidation treatment: The titanium planting substrate is used as the anode, pure titanium is used as the cathode, and the electrolyte is an ethylene glycol solution containing 0.4wt% NH4F and 2.5vol% water. The anodic oxidation treatment is carried out at a constant voltage of 50V for 20min.

[0069] (2) Ultrasonic vibration treatment: The titanium implant substrate after the first anodization was placed in deionized water and ultrasonicated at an ultrasonic frequency of 200W for 30 minutes.

[0070] (3) Second anodic oxidation treatment: The ultrasonically vibrated titanium implantation substrate is used as the anode, pure titanium is used as the cathode, and the electrolyte is an ethylene glycol solution containing 0.4wt% NH4F and 2.5vol% water. The anodic oxidation treatment is carried out at a constant voltage of 25V for 60min.

[0071] (4) Electrochemical deposition treatment: The titanium implant substrate after the second anodic oxidation treatment is used as the cathode, the platinum sheet is used as the anode, the electrolyte is an aqueous solution containing 0.05 mol / L NaNO3, 0.20 mmol / L Ca(NO3)2, 0.12 mmol / L (NH4)2HPO4, and an initial voltage of -3V. Electrochemical deposition is carried out in a water bath at 80℃ for 800s to obtain the titanium implant.

[0072] Example 3

[0073] This invention provides a titanium implant, the surface of which, from the inside out, comprises a nanotube layer, a nanogrid layer, and a calcium phosphate coating. The nanotube layer has an average diameter of 40 nm and a thickness of 350 nm. The nanogrid layer has an average diameter of 75 nm and a thickness of 15 nm. The calcium phosphate coating is a CaHPO4 coating with a thickness of 15 nm.

[0074] The preparation method of the titanium implant includes the following steps:

[0075] (1) First anodic oxidation treatment: using the titanium planting substrate as the anode, pure titanium as the cathode, and the electrolyte as an ethylene glycol solution containing 0.2wt% NH4F and 1.5vol% water, the anodic oxidation treatment was carried out at a constant voltage of 70V for 25min;

[0076] (2) Ultrasonic vibration treatment: The titanium implant substrate after the first anodization was placed in deionized water and ultrasonicated at an ultrasonic frequency of 180W for 25 minutes.

[0077] (3) Second anodic oxidation treatment: The ultrasonically vibrated titanium implantation substrate is used as the anode, pure titanium is used as the cathode, and the electrolyte is an ethylene glycol solution containing 0.2wt% NH4F and 1.5vol% water. The anodic oxidation treatment is carried out at a constant voltage of 40V for 70min.

[0078] (4) Electrochemical deposition treatment: The titanium implant substrate after the second anodic oxidation treatment is used as the cathode, the platinum sheet is used as the anode, the electrolyte is an aqueous solution containing 0.05 mol / L NaNO3, 0.20 mmol / L Ca(NO3)2, 0.12 mmol / L (NH4)2HPO4, and an initial voltage of -3V. Electrochemical deposition is carried out in a water bath at 80℃ for 800s to obtain the titanium implant.

[0079] Example 4

[0080] This invention provides a titanium implant, the surface of which, from the inside out, comprises a nanotube layer, a nanogrid layer, and a calcium phosphate coating. The nanotube layer has an average diameter of 35 nm and a thickness of 350 nm. The nanogrid layer has an average diameter of 70 nm and a thickness of 10 nm. The calcium phosphate coating is a CaHPO4 coating with a thickness of 20 nm.

[0081] The only difference between the titanium implant provided in this embodiment and that in Example 1 is that it was electrochemically deposited for 900 seconds in a water bath at 80°C.

[0082] Example 5

[0083] This invention provides a titanium implant, the surface of which, from the inside out, comprises a nanotube layer, a nanogrid layer, and a calcium phosphate coating. The nanotube layer has an average diameter of 35 nm and a thickness of 350 nm. The nanogrid layer has an average diameter of 70 nm and a thickness of 10 nm. The calcium phosphate coating is a CaHPO4 coating with a thickness of 5 nm.

[0084] The only difference between the titanium implant provided in this embodiment and that in Example 1 is that it was electrochemically deposited for 700 seconds in a water bath at 80°C.

[0085] Comparative Example 1

[0086] The present invention provides a titanium implant in a comparative example. The only difference between the preparation process of the titanium implant and that of Example 1 is that the parameters of the second anodizing treatment are consistent with the parameters of the first anodizing treatment, and the voltage of both the first and second anodizing treatments is adjusted to 60V and the time is 1h.

[0087] The titanium implant obtained in this comparative example has an average diameter of 110 nm for the nanotubes and nanogrids. However, due to the identical parameters in the two anodizing processes, the prepared nanostructures overlapped, making it impossible to distinguish between the nanotube and nanogrid structures. Specifically, it could not exhibit a structure consisting of a nanotube layer, a nanogrid layer, and a calcium phosphate coating from the inside out. The specific surface morphology is shown in the image below. Figure 10 As shown.

[0088] Comparative Example 2

[0089] The present invention provides a titanium implant in a comparative example. The only difference between the preparation process of the titanium implant and that of Example 1 is step (2). Step (2) of this comparative example is corrosion oxidation, specifically: the titanium implant substrate after the first anodization is placed in an aqueous solution of 5 vol% phosphoric acid and 1.5 g / 100 mL chromic acid and corroded for 1 h. During the corrosion oxidation process, the substrate is stirred at 350 r / min. After the corrosion oxidation is completed, the substrate is washed with anhydrous ethanol and deionized water for 5 min each.

[0090] The titanium implant obtained in this comparative example has an average nanotube diameter of 35 nm and an average nanogrid diameter of 70 nm. However, due to the corrosion and oxidation process, some of the initially formed nanotube structure is destroyed, preventing the formation of a uniform and ordered nanogrid structure. Consequently, it cannot effectively guide subsequent calcium and phosphorus deposition. Therefore, the titanium implant prepared in this comparative example cannot exhibit a structure consisting of a nanotube layer, a nanogrid layer, and a calcium and phosphorus coating from the inside out. The specific surface morphology is shown in the figure below. Figure 11 As shown; from Figure 11 As can be seen, the titanium implants prepared by the method of the present invention cannot form a uniform and ordered thin-layer nanogrid, and the nanostructure is partially destroyed.

[0091] Comparative Example 3

[0092] The present invention provides a titanium implant in a comparative example. The only difference between the preparation process of the titanium implant and that of Example 1 is step (4). The electrochemical deposition time of the comparative example is 1000s.

[0093] In the titanium implant provided in this comparative example, the average diameter of the nanotubes in the nanotube layer is 35 nm, the thickness of the nanotube layer is 350 nm, the average diameter of the nanogate in the nanogate layer is 70 nm, the thickness of the nanogate layer is 10 nm, and the calcium phosphate coating is a CaHPO4 coating with a thickness of 30 nm.

[0094] The surface morphology of the titanium implant prepared in this comparative example is shown in Figure 12. Figure 12 As can be seen, when the electrochemical deposition time is extended, the morphology of the nanotubes in the obtained titanium implant begins to become blurred.

[0095] Comparative Example 4

[0096] The present invention provides a titanium implant in a comparative example. The only difference between the preparation process of the titanium implant and that of Example 1 is step (4). The electrochemical deposition time of the comparative example is 1200s.

[0097] In the titanium implant provided in this comparative example, the average diameter of the nanotubes in the nanotube layer is 35 nm, the thickness of the nanotube layer is 350 nm, the average diameter of the nanogate in the nanogate layer is 70 nm, the thickness of the nanogate layer is 10 nm, and the calcium phosphate coating is a CaHPO4 coating with a thickness of 40 nm.

[0098] The surface morphology of the titanium implant prepared in this comparative example is shown in Figure 13. Figure 13 As can be seen, when the electrochemical deposition time is extended, the morphology of the nanotubes in the obtained titanium implants almost completely disappears.

[0099] Comparative Example 5

[0100] The present invention provides a titanium implant in a comparative example. The only difference between the preparation process of the titanium implant and that of Example 1 is step (4). The electrochemical deposition time of the comparative example is 500s.

[0101] In the titanium implant provided in this comparative example, the average diameter of the nanotubes in the nanotube layer is 35 nm, the thickness of the nanotube layer is 350 nm, the average diameter of the nanogate in the nanogate layer is 70 nm, the thickness of the nanogate layer is 10 nm, and the calcium phosphate coating is a CaHPO4 coating with a thickness of 4 nm.

[0102] Comparative Example 6

[0103] The present invention provides a titanium implant in a comparative example. The only difference between the preparation process of the titanium implant and that of Example 1 is that the parameters of the first anodizing treatment are different. The voltage of the first anodizing treatment is 80V and the time is 40min.

[0104] The titanium implant obtained in this comparative example has a nanotube layer with an average nanotube diameter of 35 nm and a nanotube layer thickness of 350 nm. The nanogate layer has an average nanogate diameter of 110 nm and a nanogate layer thickness of 10 nm. The calcium phosphate coating is a CaHPO4 coating with a thickness of 15 nm.

[0105] Comparative Example 7

[0106] The present invention provides a titanium implant in a comparative example. The only difference between the preparation process of the titanium implant and that of Example 1 is that the parameters of the second anodizing treatment are different. The voltage of the second anodizing treatment is 15V and the time is 30min.

[0107] In this comparative example, the average diameter of the nanotubes in the nanotube layer of the titanium implant is 10 nm, and the thickness of the nanotube layer is 250 nm. The average diameter of the nanogate in the nanogate layer is 70 nm, and the thickness of the nanogate layer is 10 nm. The calcium phosphate coating is a CaHPO4 coating with a thickness of 15 nm.

[0108] Comparative Example 8

[0109] The present invention provides a titanium implant in a comparative example. The only difference between the preparation process of the titanium implant and that of Example 1 is the electrochemical deposition. The electrolyte used in the electrochemical deposition of this comparative example is 0.208 mmol / L CaCl2, 0.125 mmol / L NaH2PO4 and 0.1 mol / L NaCl, and the resulting calcium phosphate coating is a hydroxyapatite coating.

[0110] Example of effect

[0111] The osseointegration ability of the titanium implants prepared in Examples 1-5 and Comparative Examples 1-8 is verified by the following steps:

[0112] (1) Experimental design: The mandibular implant for beagle dogs was designed as a threaded cylindrical implant with a diameter of 4 mm and a length of 6 mm (e.g., Figure 14 (As shown); The experiment was divided into a negative control group and an experimental group. The negative control group was a calcium phosphorus / nanotube composite layer prepared using existing technology, and the experimental group was a titanium implant prepared in Examples 1-5 and Comparative Examples 1-8 of this invention.

[0113] Specifically, the existing method for preparing the calcium-phosphorus / nanotube composite layer is as follows: using a titanium implant substrate as the anode, pure titanium as the cathode, and an ethylene glycol solution containing 0.3 wt% NH4F and 2 vol% water as the electrolyte, anodizes the substrate at a constant voltage of 30V for 1 hour; then, using the anodized titanium implant substrate as the cathode, a platinum sheet as the anode, and an aqueous solution containing 0.05 mol / L NaNO3, 0.20 mmol / L Ca(NO3)2, and 0.12 mmol / L (NH4)2HPO4 as the electrolyte, and an initial voltage of -3V, electrochemically deposits the substrate at 80℃ in a water bath for 800 seconds.

[0114] (2) Implantation surgery: Anesthesia was administered via intramuscular injection of 3% sodium pentobarbital solution (0.3 mL / kg) combined with sedative II injection (0.03 mL / kg) into the leg. The oral cavity, head, neck, and face were disinfected and draped. The second mandibular premolars to the first molars on both sides were extracted. Specifically, the gingiva was thoroughly separated, and a high-speed turbine dental handpiece (diamond bur) was used to longitudinally break the crown from the center to the root bifurcation, loosening and removing the teeth. The extraction sockets were scraped and sutured. Gentamicin sulfate injection (80,000 U / day) was administered intramuscularly for 3 days post-surgery. Three months after alveolar bone healing, the area was disinfected, anesthetized, and draped. The gingiva was incised along the alveolar ridge crest from the second premolar to the first molar, flipped, and the bone surface exposed and trimmed. A pilot drill and a reamer were used to prepare the cavity, while simultaneously rinsing and cooling with saline. The experimental sample was manually implanted using a flathead screwdriver, with the tip flush with the alveolar ridge crest, and then tightly sutured. Gentamicin sulfate injection (80,000 U / day) was administered intramuscularly for 3 days postoperatively. The treatments were administered at 4 and 8 weeks postoperatively for observation.

[0115] (3) Sampling and Testing: Samples were collected at 4 and 8 weeks post-surgery. Beagles were euthanized by injecting an excessive amount of sodium pentobarbital solution, the mandible was separated, and the surrounding soft tissue was dissected. The mandible was prepared into a bone sample containing one experimental sample using a high-speed turbine dental handpiece (diamond bur), fixed in 4% paraformaldehyde for 48 hours, and then transferred to 70% ethanol for preservation. Micro-CT was used to observe the bone integration status of the sample and compare the bone volume (BV / TV) around the sample; hard tissue sections were specially stained (methylene blue-acid fuchsin) to observe the sample-bone interface and measure the sample-bone contact ratio (BIC).

[0116] The results are shown in Table 2.

[0117] Table 2

[0118]

[0119] As can be seen from Table 2, when the technical solution of the present invention is adopted, the prepared titanium implant has higher BV / TV value and BIC value at 8 weeks, wherein the BV / TV value is above 41.62% and the BIC value is above 65.68%.

[0120] As can be seen from Examples 1, 4-5, and Comparative Examples 3-5, the deposition time in the preparation of titanium implants affects the performance of the titanium implants. When the deposition time in Comparative Examples 3-4 is too long, which is outside the range given in this invention, not only can the morphology of the nanotubes be clearly seen from the surface morphology diagram, but the osseointegration ability of the obtained titanium implants also decreases significantly. At 8 weeks, compared with Example 1, the BV / TV value in Comparative Examples 3-4 decreased by 5.03-5.39%, and the BIC value decreased by 6.77-7.11%. When the deposition time in Comparative Example 5 is too short, which is outside the range given in this invention, the osseointegration ability of the obtained titanium implants also shows a significant downward trend.

[0121] As can be seen from Example 1 and Comparative Examples 6-7, when the parameters of the first anodizing treatment and the second anodizing treatment are not within the scope of the present invention, the average diameter of the obtained nanotubes or the average diameter of the nanogrids are not within the scope of the present invention, and the bone bonding ability of the obtained products shows a significant downward trend. At 8 weeks, compared with Example 1, the BV / TV value in Comparative Examples 6-7 decreased by 5.25-5.88%, and the BIC value decreased by 7.98-8.7%.

[0122] As can be seen from Example 1 and Comparative Example 1, when the average diameters of the prepared nanotubes and nanogrids are the same, from Figure 10The provided surface morphology images cannot distinguish between the nanotube layer and the nanogate layer, and the bone integration ability of the obtained product is also significantly reduced, indicating that the structure of the nanotube layer and the nanogate layer provided by the present invention has an excellent effect on improving the bone integration ability of titanium implants.

[0123] As can be seen from Example 1 and Comparative Example 2, when the nanotubes formed by the first anodic oxidation are removed by corrosion oxidation, not only from... Figure 11 It can be found that some nanotube structures are damaged and a uniform and ordered thin-layer nanogrid structure cannot be obtained. Therefore, the bone integration ability of titanium implants also shows a downward trend.

[0124] As can be seen from Example 1 and Comparative Example 8, when the electrolyte used for electrochemical deposition is changed, the materials of the calcium phosphate coating obtained are different. Compared with Example 1, the bone bonding ability of the product prepared in Comparative Example 8 is significantly reduced.

[0125] In addition, animal experiments were conducted on the negative control group (AOC) and the titanium implant (DAOC) prepared in Example 1. Micro-CT three-dimensional reconstruction models were performed at 4 weeks and 8 weeks, respectively, and the results are as follows. Figure 15 As shown, where Figure 15 The medium yellow represents the bone tissue surrounding the implant; animal experiments were conducted on the negative control group and the titanium implants prepared in Example 1. Hard tissue sections were stained with methylene blue-acid fuchsin at 4 and 8 weeks, and the results are as follows. Figure 16 As shown; where red represents bone tissue,

[0126] from Figure 15-16 As can be seen, compared with implants prepared by existing technologies, when the implants of the present invention are implanted into the mandible of beagle dogs for 4 and 8 weeks, there is more bone around the implant and the bone-implant contact rate is higher at 4 weeks. This indicates that the surface of the implant prepared by the technical solution of the present invention has a good effect on accelerating bone integration.

[0127] Finally, it should be noted that the above embodiments are used to illustrate the technical solutions of the present invention and not to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A titanium implant, characterized in that, The surface of the titanium implant comprises, from the inside out, a nanotube layer, a nanogate layer, and a calcium phosphate coating. The nanotubes in the nanotube layer have an average diameter of 30-35 nm and a thickness of 350-400 nm. The average diameter of the nanogate in the nanogate layer is 60-70 nm, and the thickness of the nanogate layer is 10 nm. The calcium-phosphorus coating is a CaHPO4 coating, and the thickness of the calcium-phosphorus coating is 15 nm. The average diameter of the nanogates in the nanogate layer is more than twice the average diameter of the nanotubes in the nanotube layer; The preparation method of the titanium implant includes the following steps: After the first anodizing of the titanium implant substrate surface, ultrasonic vibration was performed, followed by a second anodizing and electrochemical deposition to obtain a titanium implant. In the electrochemical deposition, the electrochemical deposition temperature is 70-90℃ and the electrochemical deposition time is 700-900s.

2. The titanium implant according to claim 1, characterized in that, In the first anodic oxidation, the anode is a titanium implantation substrate, the cathode is pure titanium, the electrolyte is an ethylene glycol solution containing 0.2-0.4wt% NH4F and 1.5-2.5vol% water, the oxidation voltage is 50-70V, and the oxidation time is 15-25min.

3. The titanium implant according to claim 1, characterized in that, During the ultrasonic oscillation, the ultrasonic power is 180-200W and the ultrasonic time is 25-35min.

4. The titanium implant according to claim 1, characterized in that, In the second anodic oxidation, the anode is a titanium implantation substrate subjected to ultrasonic vibration, the cathode is pure titanium, the electrolyte is an ethylene glycol solution containing 0.2-0.4wt% NH4F and 1.5-2.5vol% water, the oxidation voltage is 20-40V, and the oxidation time is 50-70min.

5. The titanium implant according to claim 1, characterized in that, In the electrochemical deposition, the anode is platinum, the cathode is a titanium implantation substrate after second anodic oxidation, the electrolyte is an aqueous solution containing 0.04-0.06 mol / L NaNO3, 0.18-0.22 mmol / L Ca(NO3)2 and 0.10-0.14 mmol / L (NH4)2HPO4, and the initial potential is (-2)-(-4) V.

6. The application of the titanium implant as described in claim 1 in the preparation of medical implant materials.

Citation Information

Patent Citations

  • Anodization of implant materials

    WO2025189125A1